Complexity of Treatment Regimens and Patient Adherence in Individuals with Heart Failure in Yemen: A cross Sectional Study - Abdullah, Ramez; Rahmawati, Fita; Widayanti, Anna Wahyuni (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Various studies have consistently found that increased complexity in medication regimens leads to poorer adherence. Recognizing the growing global prevalence of heart failure and the specific challenges it presents, especially in low-resource settings, this study aims to investigate the influence of complexity of treatment regimens on adherence levels among Individuals with heart failure in Yemen. Through a cross-sectional observational study conducted at three major hospitals in Sana’a, structured questionnaires were employed to assess self-reported medication adherence and regimen complexity. The findings reveal a significant negative association between higher regimen complexity and adherence with regression coefficient (B = -0.150; P value 0.020). Moreover, socioeconomic factors such as income (B = 2.753; P value 0.000) and employment status (B = -1.380; P value 0.006) were found to exert considerable influence on adherence levels. This study underscores the imperative for simplified medication regimens and improved patient education to enhance adherence rates among heart failure patients in developing nations.